Colloidal tectonics for tandem synergistic Pickering interfacial catalysis: oxidative cleavage of cyclohexene oxide into adipic acid. Issue 2 (22nd October 2018) - Yang, Bingyu; Leclercq, Loïc; Schmitt, Véronique; Pera-Titus, Marc; Nardello-Rataj, Véronique
Abstract : Supramolecular preorganization can provide useful architectures for colloidal building and catalytic applications. Abstract : Supramolecular preorganization and interfacial recognition can provide useful architectures for colloidal building. To this aim, a novel approach, based on colloidal tectonics involving two surface-active particles containing both recognition and catalytic sites, has been developed for controlling the formation and the properties of Pickering emulsions. This was illustrated by the combination of dodecyltrimethylammonium phosphotungstate nanoparticles, [C12 ]3 [PW12 O40 ], and silica particles functionalized with alkyl and sulfonic acid groups, [C n /SO3 H]@SiO2 . The interfacial self-assembly occurs by the penetration of the alkyl chains of [C n /SO3 H]@SiO2 into the [C12 ]3 [PW12 O40 ] supramolecular porous structure constituted of polar and apolar regions. The emulsions were used as a non-nitric acid route for adipic acid synthesis from the one-pot oxidative cleavage of cyclohexene oxide with aqueous H2 O2 . The catalytic performance was significantly boosted due to the synergistic interactions between the particles.